Religious, Commercialization, and Gender Discrimination: Study of Poligamy Mentoring KH. Khafidzin on Social Media - Eka Putri, Nerisma; Bachrul Falah, Mohammad; Azkia Fahmi, Muhammad; Rahmatan Hanif, Randu; Ali Junid, Khaidir (LAKPESDAM MWCNU Palengaan, 2025)
The study aims to uncover forms of gender discrimination in Hafidzin's polygamy campaign on social media, as well as reveal the sacrality of religion as a result of its commercialization. This research employs a qualitative approach, collecting netnographic data. The results showed that Hafidizn's Polygamy Mentoring program contained three types of gender discrimination: marginalization, subordination, and stereotypes. The Hafidzin commercialized polygamy campaign also dismisses religious sacrality values, which are the primary purpose of polygamy to protect the weak, and the purpose of marriage, which may make divorce more difficult. Penelitian ini bertujuan untuk mengungkap bentuk-bentuk diskriminasi gender dalam kampanye poligami Hafidzin di media sosial, serta mengungkap kesakralan agama sebagai akibat dari komersialisasinya. Penelitian ini menggunakan jenis penelitian kualitatif dengan metode pengumpulan data netnografi. Hasil penelitian menunjukkan bahwa program bimbingan poligami Hafidzin mengandung tiga jenis diskriminasi gender: marginalisasi, subordinasi, dan stereotip. Kampanye poligami komersial Hafidzin juga menghilangkan nilai-nilai kesakralan agama yang merupakan tujuan utama poligami untuk melindungi yang lemah dan tujuan pernikahan yang dapat membuat perceraian menjadi lebih sulit.